2007
DOI: 10.1089/rej.2006.0513
|View full text |Cite
|
Sign up to set email alerts
|

The Olive Constituent Oleuropein Exhibits Proteasome Stimulatory Properties In Vitro and Confers Life Span Extension of Human Embryonic Fibroblasts

Abstract: Normal human fibroblasts undergo replicative senescence due to both genetic and environmental factors. Senescence and aging can be further accelerated by exposure of cells to a variety of oxidative agents that contribute among other effects to the accumulation of damaged proteins. The proteasome, a multicatalytic nonlysosomal protease, has impaired function during aging, while its increased expression delays senescence in human fibroblasts. The aim of this study was to identify natural compounds that enhance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 50 publications
2
145
0
12
Order By: Relevance
“…5 oxidant activity of OLE was also determined in human leukemic cell line (Jurkat) (Fares et al, 2011). Again, OLE decreased the intracellular levels of reactive oxygen species (ROS) in human embryonic fibroblasts and H 2 O 2 -exposed in insulin secreting β-cells (Katsiki et al, 2007;Cumaoglu et al, 2011). Thus, OLE could modulate the PM-induced genetic and oxidative damage by preventing free radical generation or by stimulating components of the antioxidant defense system.…”
Section: Discussionmentioning
confidence: 96%
“…5 oxidant activity of OLE was also determined in human leukemic cell line (Jurkat) (Fares et al, 2011). Again, OLE decreased the intracellular levels of reactive oxygen species (ROS) in human embryonic fibroblasts and H 2 O 2 -exposed in insulin secreting β-cells (Katsiki et al, 2007;Cumaoglu et al, 2011). Thus, OLE could modulate the PM-induced genetic and oxidative damage by preventing free radical generation or by stimulating components of the antioxidant defense system.…”
Section: Discussionmentioning
confidence: 96%
“…Vitamin E (Packer et al, 1974), kinetin Clark, 1994), carnosine (McFarland andHolliday, 1994) and garlic (Svendsen et al, 1994) are few examples of natural compounds that have been shown to exert a pro-longevity effect on human primary cultures. More importantly, natural substances that possess proteasome activating properties like oleuropein (Katsiki et al, 2007) have been also shown to promote lifespan extension. Given these findings, we sought to investigate the role of QUER, a potent, natural anti-oxidant, on survival and lifespan of human fibroblasts along with its possible effects on the main secondary antioxidant mechanism, the proteasome.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It is responsible for the cellular clearance from damaged and oxidized proteins that may cause deleterious side effects upon lack of proteolysis and aggregation. Given that we have already shown that the proteasome can be activated either through genetic means or through natural means (Katsiki et al, 2007) endowing the cells with an enhanced survival capacity against oxidative stress and an extended lifespan, we have examined whether QUER as a potent antioxidant agent may stimulate the proteasome function. We show that CT-L proteasome activity and content are induced upon QUER treatment in HFL-1 human primary cells.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleuropeine showed positive effect on 20S proteasome activity and on senescence of embryonic human fibroblasts. Although the activation rate was only of 1.2 fold, it was the first study to suggest that protea some activators might have the potential to be developed into anti-aging agents [24]. Our work attempts to enhance this theory.…”
Section: Discussionmentioning
confidence: 96%